"Not the Almighty": Evaluating Aboriginal Influence in Northern Land-Claim Boards - White, Graham (ARCTIC, 2009)
The settling of comprehensive land claims across Canada’s territorial North has brought about substantial changes in governance. Prominent among these has been the establishment of numerous regulatory and co-management boards dealing with land, wildlife, and environmental issues. These boards were explicitly designed to bring significant aboriginal influence to bear in key land and wildlife decisions. To examine whether the boards have enhanced aboriginal participation and influence in these decision-making processes, factors such as the number and influence of aboriginal board members, the extent of board powers, the independence (financial and otherwise) of the boards, and the boards’ willingness and capacity to incorporate traditional knowledge into their operations are considered. Overall, the evidence supports the conclusion that the land-claim boards represent an important vehicle for substantially enhanced aboriginal involvement in and influence over government decisions affecting the wildlife and environment of traditional aboriginal lands. Le règlement d’importantes revendications territoriales dans les territoires canadiens du Nord s’est traduit par des changements considérables en matière de gouvernance. L’un de ces changements les plus importants a consisté en l’établissement de nombreux conseils de réglementation et de cogestion s’occupant de questions ayant trait aux terres, à la faune et à l’environnement. Ces conseils ont été explicitement conçus pour que les Autochtones exercent une plus grande influence sur les décisions relatives aux terres et à la faune. Afin d’examiner si ces conseils ont permis d’améliorer la participation des Autochtones et de rehausser l’influence qu’ils ont sur la prise de décisions, divers facteurs tels que le nombre et l’influence des membres autochtones aux conseils, l’étendue des pouvoirs des conseils, l’autonomie (financière ou autre) de même que la volonté et la capacité des conseils à intégrer les connaissances traditionnelles à leur exploitation entrent en ...